Associations between dynamic change of Chinese visceral adiposity index and hypertensive co-morbidities in the middle-aged and elderly population: a Chinese prospective cohort study - Jinjian Xu; Yingdi Yang; Ye Hu; Yingxiang Song; Xiao Ye; Yu-ming Chen; Hanbing Li; Xiaohong Wu (Frontiers in Nutrition, 2025)
Background and aimsThe non-invasive Chinese visceral adiposity index (CVAI) was linked to the risk of cardiovascular disease and mortality. The associations of the CVAI and its longitudinal changes with hypertension and related comorbidities remain poorly understood. This study aims to examine the associations between CVAI, its trajectories, and hypertensive comorbidities.MethodsThis study included 5,058 participants from the China Health and Retirement Longitudinal Study (CHARLS), with baseline data collected in 2011–2012. Participants were subsequently followed across four waves: 2013–2014, 2015–2016, 2017–2018, and 2019–2020. Study outcomes included hypertension (HTN) and its comorbidities: overweight (HTN-OW), metabolic unhealthiness (HTN-MET), and diabetes (HTN-DM). Prospective associations between baseline CVAI and these outcomes were analyzed using Cox regression. Longitudinal trajectories of CVAI over 3 years (2012–2015) were identified through K-means clustering analysis.ResultsFrom 2013 to 2020, 1,581 participants (31.3% of the 5,058 total) developed HTN. The higher CVAI was significantly associated with risk of HTN (HR per 1 SD increase = 1.20; 95% CI: 1.08–1.33) and hypertensive co-morbidities (HTN-OW, HTN-MET, and HTN-DM) (HR = 1.20–1.38, p < 0.01). Both per-quartile increment in CVAI and cumulative CVAI showed significant positive associations with HTN risk and its comorbidities (all p-trend < 0.05). K-means clustering analysis generated three trajectories of change in CVAI levels (low, moderate, and high) between 2012 and 2015, and higher class was significantly associated with risk of HTN and co-morbidities compared to low class (HR = 1.63∼1.65, p < 0.05, p-trend < 0.05).ConclusionThe findings highlight the significant positive correlation between the change in CVAI with hypertension and comorbidities in the middle-aged and elderly population, suggesting a potential application in the clinical assessment and prevention of cardiometabolic disease.